A critical assessment of institutions, roles and leverage in public policymaking : Ethiopia, 1974-2004 - Abebe Wolde, Mulugeta (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (School of Public Management and Planning ))—University of Stellenbosch, 2005.